Preservation of plant‐wax biomarkers in deserts: implications for Quaternary environment and human evolutionary studies - Deepak Kumar Jha; Robert Patalano; Jana Ilgner; Hema Achyuthan; Abdullah M. Alsharekh; Simon Armitage; James Blinkhorn; Nicole Boivin; Paul S. Breeze; Ravindra Devra; Nicholas Drake; Huw S. Groucutt; et al. (Journal of Quaternary Science, 2024)
Analysis of plant‐wax biomarkers from sedimentary sequences can enable past environmental and hydrological reconstruction and provide insights into past hominin adaptations. However, biomarker preservation in desert contexts has been considered unlikely given the sparse nature of the vegetation within the landscape. Here we evaluate the preservation of n ‐alkanes and fatty acids collected from four depositional sequences associated with archaeological contexts in the Nefud Desert, Saudi Arabia, and the Thar Desert, India. Pleistocene and Holocene samples were selected to understand the effects of age on preservation. The results of molecular distribution patterns and indices, particularly the high carbon preference index and average chain length, show the preservation of plant‐wax biomarkers in both the Holocene and Pleistocene desert sequences, while δ 13 C values and organic content provide insights into the vegetation contributing to the plant‐wax organic pool. This study provides a baseline for understanding human–environment interactions and for reconstructing changes in arid land habitats of relevance to hominins during the Quaternary.